Psychological meaningfulness at work as a mediator of job characteristic and job attachment in public elementary schools in Yogyakarta - Welly Putri Akmadelita; Erika Setyanti Kusumaputri (Department of Psychology, Universitas Negeri Yogyakarta, 2018)
This study aims to determine the relationship between job characteristics toward work engagement through the mediating psychological meaningfulness. Subjects in this study were a primary school teacher in Yogyakarta who totaled 132 (N=132) of teachers. Our data was collected using the work engagement scale (vigor, dedication, and absorption), job characteristics scale (skill variety, task identity, task significance, autonomy, and feedback), and psychological meaningfulness scale (meaningful work, others around the work environment, the work context, and spiritual life) — the methods of data analysis used path analysis techniques developed from regression analysis. Results of path analysis indicated that indirect effect was significant (p2 0.332 x 0.332 = 0.110) and the direct effect of 0511. Therefore, the total effect of the work engagement is direct and indirect effect that is 0.511 + 0.110 = 0.621 (62.1%). This means that hypotheses were accepted, there is a correlation between job characteristics toward work engagement through psychological meaningfulness as a mediator, where the suitability of job characteristics will improve work engagement through psychological meaningfulness as a mediator, where the suitability of job characteristics will improve work engagement through psychological meaningfulness that also higher on the teacher.